1961
DOI: 10.1111/j.1479-828x.1961.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Use of Bretylium Tosylate in Pregnancy

Abstract: Summary The use of bretylium tosylate in hypertensive pregnant women is discussed. Using C‐14 labelled material there is evidence of placental transfer but this does not appear to affect the foetus adversely. In 12 patients, Darenthin adequately controlled the blood pressure of both essential hypertension complicating pregnancy and pre‐eclampsia. There is insufficient evidence to show whether or not this control improves foetal prognosis or modifies other manifestations of toxaemia. In 1 patient, therapy was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1963
1963
1963
1963

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…(b) Post-ganglionic drugs: Studies with C1'-labelled bretylium iodide have shown that this preparation crosses the placenta and can be found in liquor and in foetal blood of both animals and human (Whiley et al, 1961). There is no evidence that this has any significance with regard to foetal welfare.…”
Section: Hypotensive Drugsmentioning
confidence: 99%
“…(b) Post-ganglionic drugs: Studies with C1'-labelled bretylium iodide have shown that this preparation crosses the placenta and can be found in liquor and in foetal blood of both animals and human (Whiley et al, 1961). There is no evidence that this has any significance with regard to foetal welfare.…”
Section: Hypotensive Drugsmentioning
confidence: 99%